Guidance And Counseling For Local Culture-Based Industries In The Context Of Modern Indonesia's Multicultural Workforce - Marsela Dominika Negor; Paskalia Osda Wardani; Tina Anggriani; Amelia Yupita; Rahmah Rahmah; Karyanti Karyanti; Asep Solikin; M. Fatchurrahman (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Background: The workforce's cultural diversity is a social reality increasingly prominent in the industrial world and has direct implications for the need for guidance and counseling services. Aim: This study analyzes the characteristics of the workforce's cultural background and their implications for the development of adaptive, multicultural industrial guidance and counseling services. Method: The research uses a descriptive, quantitative approach with labor subjects from various ethnic backgrounds. Data were collected through demographic questionnaires and analyzed using descriptive statistics to illustrate the distribution of respondents' cultural characteristics. Results and Discussion: The results showed a dominance of local culture alongside the diversity of minority cultural groups, which affected work values, career orientation, and the need for counseling services. The discussion revealed that industry guidance and counseling need to integrate local cultural values while implementing a multicultural approach to make services more inclusive and contextual. The study's conclusions confirm that the effectiveness of industry guidance and counseling is largely determined by counselors' cultural sensitivity and multicultural competence. Conclusion: This study recommends developing a guidance and industry counseling model grounded in local context and cultural diversity, and conducting follow-up research with a more comprehensive design.